Practical dynamic matrix control for thermal power plant coordinated control. (February 2018) - Moon, Un-Chul; Lee, Youngjun; Lee, Kwang Y.
Abstract: This paper proposes three practical strategies for the coordinated control (CC) of a thermal power plant using dynamic matrix control (DMC) that can be directly applied to industrial power plants. The three strategies are the replacement of conventional CC using DMC, the inclusion of disturbance variables, and a supplementary reference correction of the conventional CC. The performance during wide range operation of the three DMC–CCs is compared and discussed with the simulation results of a large-scale power plant model. Highlights: Practical coordinated controls for thermal power plant are proposed. Three different structures using Dynamic Matrix Control are compared. Three Dynamic Matrix Controls show effective than conventional control. Measured disturbance using local control action shows better performance.